Early Assessment and Identification of Children with Special Needs to Support Inclusive Education - Lestari, Ana; Damayanti, Rifana; Meilana, Septi Fitri (Holistic Science, 2025)
Assessment and early identification play a crucial role in supporting inclusive education for children with special needs (CSN). This study aims to explore assessment methods, the identification of children's characteristics, and effective learning strategies in the context of inclusive education. A case study was conducted on a CSN student at SDN Baru 06 Pagi, utilizing observation, interviews, and multidisciplinary collaboration to identify the student's needs. The findings reveal that a collaborative approach involving teachers, parents, and psychologists positively impacts the learning process of CSN. However, challenges such as limited teacher training and a lack of formal assessment tools remain significant barriers. Recommendations include providing specialized training, procuring formal assessment tools, and implementing policies that support inclusive education.